Rwanda : Sixth Review Under the Policy Support Instrument and Request for Extension of the Policy Support Instrument-Staff Report; Press Release. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2013)
Rwanda has responded to lower aid by tightening policies and drawing on its foreign reserves to cushion the impact on the economy. Economic activity has been resilient despite lower aid inflows. The agreed framework for the FY2013/14 budget is in line with Policy Support Instrument (PSI) objectives. The government's intention to develop a comprehensive plan for enhancing domestic revenue mobilization over the medium term is timely. Rwanda's new poverty reduction strategy (EDPRS2) and the commitment to tighten the monetary stance while allowing greater exchange rate flexibility is encouraging.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet